Mediation of coping style between academic self-efficacy and academic stress in middle school students - Sun, Pu; Wang, Lifang; Yan, Ling (Frontiers in Psychology, 2025)
ObjectiveTo explore the mediating role of coping styles between academic self-efficacy and academic stress among middle school students and to provide insights into potential intervention strategies to alleviate academic stress.MethodsA total of 2,720 middle school students participated in the survey, which utilized the Academic Self-Efficacy Scale, Academic Pressure Scale, and Simplified Coping Style Questionnaire. The sample included 1,336 boys (49.1%) and 1,384 girls (50.9%), with ages ranging from 11 to 18 years and an average age of 14.48 ± 1.47 years.ResultsAcademic stress was negatively correlated with academic self-efficacy and positive coping style (r = −0.37, −0.3, p < 0.001), and positively correlated with negative coping style (r = 0.32, p < 0.001). Both coping styles significantly mediated the relationship between academic self-efficacy and academic stress, with positive and negative coping accounting for 47.38 and 18% of the total effect, respectively.ConclusionAcademic self-efficacy has both direct and indirect effects on academic stress, with coping styles playing a critical mediating role. These findings suggest that fostering academic self-efficacy and encouraging positive coping strategies can effectively alleviate academic stress, providing insights for intervention programs aimed at promoting student wellbeing.